ANALISIS PERBANDINGAN LOGO X DAN TWITTER DENGAN PENDEKATAN SEMIOTIKA - Nurcholiq, Rini; Muhammad Adi Sukma Nalendra; Dinda Okta Dwiyanti Ridwan Gucci (JURNAL RUPA MATRA, 2024)
It is about the comparative semiotic analysis of X logo and Twitter logo. In this paper, the purpose of this research is to find out the meaning of icons, indexes, and symbols contained in the X logo and Twitter logo. In addition to the meaning, the author wants to know what values each logo, Twitter and X, carries. The author also wants to know what happened to the public's response to the change of the Twitter logo to X. The author uses a descriptive qualitative method with a semantic approach. The author uses a descriptive qualitative method with a semiotic approach to find out these points. In this research, the author will compare the meaning of icons, indexes, and symbols in the X logo and Twitter logo. This research is expected to provide a deeper understanding of the meaning of the X logo and Twitter logo from a semiotic perspective. Keywords: Semiotics, Communication, X Logo, Twitter Logo, Comparison